Fungal bioconversion of old oil-palm trunks by enzymatic hydrolysis on development of alternate energy source - Lee Kok Chang; Takamitsu Arai; Akihiko Kosugi; Darah Ibrahim; Panida Prawitwong; Yutaka Mori (Syiah Kuala University, 2012)
The progressive depletion of fossil fuels has been causing increasing concern on rising energy consumption and environmental issues, such as greenhouse gas emission (GHG) and global warming. Due to low productivity of oil-palm tree after 20 - 25 years, the trees passed their economic age followed by the cutting-activity for replanting. Consequently, the old oil-palm trunks are one of the most abundantly available renewable resources produced, especially by Indonesia and Malaysia. We found that the felled oil palm trunk contains large quantity of sap with high concentration of free sugar contents. The oil-palm trunk residues which are the residual substances after squeezing sap will be discharged in large quantity. Composition analysis revealed that oil-palm residues mainly consisted of 73.12% holocellulose (cellulose and hemicellulose) and 24.6% of lignin. We tried the screening of filamentous fungus which can produce high-activity enzyme against oil-palm trunk residues as feedstock of bioethanol production. A filamentous fungus, which is Penicillium rolfsii with strong activity against oil-palm trunk residues was selected for saccharification experimental study. The result showed that higher amount of sugar production was achieved comparing to the commercial enzymes (Celluclast 1.5L and Accellerase®1500) on hydrolysis of oil palm residues, which is 1 to 2-fold of higher activity. Hence, Penicillium rolfsii have attracted a great deal of interest as oil-palm residues degrader due to their superiority activity against commercial enzymes.